Fate and Transport of Microplastic Particles in Small Highway-Adjacent Streams - A case study in Gothenburg region - Hagström, Sara (My University, 2021)
A large portion of the plastics contaminating the watercourses and oceans are the so called microplastics, derived from wear and tear of tyres. There is a lack of knowledge on where the microplastic particles are deposited. Therefore, the aim of this thesis is to present an estimation of the microplastic sources and sinks in a small case study stream crossing a rural highway. This is done based on a literature review of the transportation behaviour of road related microplastics and the surrounding environment factors affecting the fate and transport, and by building a compartment model of the case study stream. To model the water pathways in connection to the case study road stretch between Jonsered and Lerum in western Sweden, the hydrological modelling tool SWAT was used, simulating the time dependent flow in the stream. With the SWAT modelled values as input data, a compartment model based on Stoke’s law in combination with Hazen’s surface loading theory was set up with the most affecting and feasible factors included. The factors included were road entrapment, wind transport, verge removal and settling of particles in the water phase. The model was built on a combination of field studies of the flow conditions and stream dimensions. Four scenarios based on real dates were simulated to show seasonal differences and to estimate the exposure of the natural environment in the area to the microplastics. To gain information about the impact of each factor, eight sensitivity analysis scenarios were set up, analysing each factor compared to a baseline scenario. The particles were shown to deposit early in the system, and only the particles in the smallest range remained suspended in the water leaving the stream. The exposure to microplastics was simulated to be highest during the winter half-year, when the wear rate of tyres is increased and the flow in the stream is generally higher. Also, the number of antecedent dry days was shown crucial for the concentration in the outgoing road runoff and hence for the exposure of microplastics in the stream. Knowing the fate and transport of microplastics in the environment is essential to assess the scale of the problem, and to build a base for implementation of microplastic reduction measures for a cleaner environment.
Keywords: microplastics; water quality modelling; Compartment modelling; hydrological modelling; SWAT-modelling; stormwater